Penerapan Project-Based Learning untuk Meningkatkan Kesadaran Moral dalam Mengikuti Suara Hati Fase E Kelas X SMA Negeri 13 Medan - Kristian Bambang; Nerita Setianingtiyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This Classroom Action Research (CAR) aims to enhance students’ moral awareness in following their conscience through the implementation of the Project-Based Learning (PjBL) model in Phase E Grade X students of SMA Negeri 13 Medan. The main issue addressed in this study is the low level of students' moral awareness in making decisions based on their conscience in daily life. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection methods included observation, interviews, documentation, and student performance assessments. The results showed that the implementation of the project-based learning model effectively improved students’ moral awareness, as evidenced by increased active participation, personal reflection on their actions, and the ability to connect learning materials with real-life experiences. Therefore, PjBL is proven to be effective in fostering students’ moral awareness through contextual and meaningful learning processes.